Studi Keanekaragaman Gastropoda Sebagai Bioindikator Perairan di Pantai Sialang Buah Kabupaten Serdang Bedagai Provinsi Sumatera Utara - Beby Aulia Kesuma Wardani; Ipanna Enggar Susetya (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Sialang Buah Beach is a coastal area which of the waters used by the comunity for doing household activitiy, fishing activity and tours activity. Activities carried out at Sialang Buah Beach will influence gastropods variety and the water quality at the beach. Gastropods as organisms live at the waters are very sensitive to the alteration of water quality where they live. The degradation of water quality will reduce the wealth of natural resources in the waters. This study aimsed to discover gastropods variety as well as waters condition at Sialang Buah Beach District of Serdang Berdagai North Sumatera Province viewed from ABC curve and Storet Index. This Study was conducted between April – May 2018 applying purposive sampling method divided to 3 stations. The result showed that the Index of diversity (H’) was in “modrate” category, index of evennes (E) was in “high” category and index of dominance was in “no dominance”. And according PP No. 82 Year 2001 About The Management of Water Quality and Water Pollution Control, and by using Storet Index reveal that the water condition at Sialang Buah Beach declared as contamined in “medium” category and based on ABC curve (Abundance and Biomass Comparison) reveal that the water condition declared as contamined in “medium” category with the density curve and the biomass overlapping each other.Key Words: Sialang Buah Beach, Gastropods, ABC Curve, Storet Index